THE INVENTORY OF THE CUSTOMERS’ ACCOUNTS RECEIVABLE AND ITS INFLUENCE ON THE PERIOD OF LIMITATION - ELENA Astakhova; ANZHELA Vasilyeva (Учёт. Анализ. Аудит, 2019)
One of the most topical problems of economic entities in modern operating conditions is an increase in accounts receivable and defaults on payments. The financial stability of business largely depends on the cash inflow which is necessary for its normal functioning. This is precisely why the issues of management and control over receivables are very significant. In order to prevent undesired effects, including financial losses owing to the refusal of debtors to pay their debts, the company should establish an effective system of control over accounts receivable. An inventory of the company’s liabilities plays an important role in this process. Therefore, this research focuses on the accounts receivable management and control over it. It also includes the issues of the accounts reconciliation statements which are prepared to extend the limitation period for the debts of the debtor.